2022
DOI: 10.31083/j.jin2105124
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic Effect of Satureja montana Dry Extract and its Active Compounds Rosmarinic Acid and Carvacrol in Acute Stress Experimental Model

Abstract: Background: Anxiety disorders are an important not only medical, but also social problem, affecting approx. 300 million people worldwide in 2019. Medications used in the treatment of anxiety are associated with many adverse reactions, which explains the increased use of herbal products as anxiolytics. Methods: An anxiolytic activity of Satureja montana, rosmarinic acid and carvacrol after 14-day long administration on an animal model of acute stress was studied. For measurement of anxiolytic effect elevated pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
3
0
2
Order By: Relevance
“…Wang and co-workers evaluated the antidepressant potential of RA in a rodent model of post-stroke depression and found that, in addition to the beneficial cellular and biochemical effects on infarct volumes and oxidative stress and damage, RA treatment resulted in a significant alleviation of depressive behavior as assessed by forced swim and sucrose preference tests (Wang, Hsieh, et al, 2021;. Lastly, anxiolytic effects of RA, as assessed by elevated plus maze and social interaction tests has recently been confirmed in a rat model of acute cold-induced stress (Vilmosh et al, 2022).…”
Section: Neuropsychiatric Stress and Depressionmentioning
confidence: 92%
“…Wang and co-workers evaluated the antidepressant potential of RA in a rodent model of post-stroke depression and found that, in addition to the beneficial cellular and biochemical effects on infarct volumes and oxidative stress and damage, RA treatment resulted in a significant alleviation of depressive behavior as assessed by forced swim and sucrose preference tests (Wang, Hsieh, et al, 2021;. Lastly, anxiolytic effects of RA, as assessed by elevated plus maze and social interaction tests has recently been confirmed in a rat model of acute cold-induced stress (Vilmosh et al, 2022).…”
Section: Neuropsychiatric Stress and Depressionmentioning
confidence: 92%
“…The dried methanolic extract from S. montana leaves was demonstrated to have significant anxiolytic activity in rats. Carvacrol and rosmarinic acid, used as controls, only showed a moderate anxiolytic effect in some tests [347]. Satureja genera essential oil may act as a neuroprotective agent in the early stage of Alzheimer's disease [348], as well as S. marianum extracts [165].…”
Section: Neurological Disorders and Wild Plantsmentioning
confidence: 97%
“…The antioxidant system consists of many enzymes, such as catalase (CAT), superoxide dismutase (SOD), glutathione (GSH) and the product of lipid peroxidation malondialdehyde (MDA), which play a pivotal role in oxidative stress. [ 28 ]. Antioxidants scavenge free radicals, protecting humans from oxidative stress [ 29 ], and act as reducing agents, oxidizing themselves by slowing the oxidation process; they include ascorbic acid and polyphenols [ 27 ].…”
Section: Introductionmentioning
confidence: 99%